2018
DOI: 10.1186/s12871-018-0632-3
|View full text |Cite
|
Sign up to set email alerts
|

Propofol vs. inhalational agents to maintain general anaesthesia in ambulatory and in-patient surgery: a systematic review and meta-analysis

Abstract: BackgroundIt is unclear if anaesthesia maintenance with propofol is advantageous or beneficial over inhalational agents. This study is intended to compare the effects of propofol vs. inhalational agents in maintaining general anaesthesia on patient-relevant outcomes and patient satisfaction.MethodsStudies were identified by electronic database searches in PubMed™, EMBASE™ and the Cochrane™ library between 01/01/1985 and 01/08/2016. Randomized controlled trials (RCTs) of peer-reviewed journals were studied. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 49 publications
5
107
3
2
Order By: Relevance
“…A meta-analysis also related better perception of the quality of postoperative recovery in the TIVA group, which was attributed to lower frequency of PONV, agitation, and postoperative pain [6]. However, the methodological heterogeneity of the studies may explain the difference between the results obtained in that meta-analysis and our study.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…A meta-analysis also related better perception of the quality of postoperative recovery in the TIVA group, which was attributed to lower frequency of PONV, agitation, and postoperative pain [6]. However, the methodological heterogeneity of the studies may explain the difference between the results obtained in that meta-analysis and our study.…”
Section: Discussioncontrasting
confidence: 41%
“…The two most commonly used general anesthesia techniques are total intravenous anesthesia (TIVA) and balanced general anesthesia (BGA), with intravenous anesthesia combined with inhalation anesthesia [5]. The use of TIVA has increased recently; this technique has been reported to provide a better experience and higher levels of patient satisfaction in outpatient and inpatient surgeries, possibly because of a lower incidence of pain, agitation, and postoperative nausea and vomiting (PONV) [6]. Studies on the quality of postanesthetic and postoperative recovery have mainly focused on measures such as recovery time, cardiorespiratory complications, pain, PONV, hospital length of stay, and other complications [7].…”
Section: Introductionmentioning
confidence: 99%
“…A large meta‐analysis revealed a significant and clinically relevant 39% reduction in postoperative nausea and vomiting with the use of propofol over inhaled anesthetic agents 15 . Propofol was also associated with lower postoperative pain scores and requirement for analgesia, which are important determinants of patient dissatisfaction 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Sevo urane is a commonly used volatile anesthetic that exhibits rapid pharmacokinetic properties. Schraag et al [20] reported that the time to respiratory recovery and tracheal extubation were shorter with sevo urane than with propofol. Moreover, SPI-guided analgesia has been demonstrated to be effective during general anesthesia with volatile anesthetics (e.g.…”
Section: Discussionmentioning
confidence: 99%